ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN KOMPENSASI RUGI FISKAL TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI LOGAM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017) - Heni Yusnita, M.Ak.; Pratiwi Nursehah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aimed to test and provide empirical evidence of the influence of profitability, firm size and fiscal lost compensation on tax avoidance. This study classified as causative research. The population in this study was manufacturing companies listed on Indonesian Stock Exchange in 2013 until 2017. The sample was chosen by purposive sampling method and after reduces with several criteria, 13 firms are determined as samples. Data used was secondary data obtained from www.idx.co.id. Data was analyzed by using a linear regression analysis with help a program named SPPS version 25. The results showed that : 1) profitability has a significant effect on tax avoidance. 2) firm size has a significant effect on tax avoidance. 3) fiscal lost compensation has significant effect on tax avoidance. The tests are based on confidence level of 95%, and an error rate of 5%.